PENGARUH PERTUMBUHAN EKONOMI TERHADAP TINGKAT PENGANGGURAN TERBUKA DI INDONESIA : THE EFFECT OF ECONOMIC GROWTH ON THE LEVEL OF OPEN UNEMPLOYMENT IN INDONESIA - Nazma, Nazma Aktatusyaniah; Natasya, Natasya Lailatul Qodriyah; Arifudin (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
Economic development and the level of open poverty are two crucial factors that are interrelated in the economic context of a country. This research aims to understand the relationship between economic development, which is calculated through indices such as Gross Domestic Product (GDP), and the level of open poverty in Indonesia. Quantitative methods are the collection of secondary data published by other parties within a certain period. The type of data used in this research is secondary data, namely information obtained simultaneously from public institutions as well as institutions related to this research. The data is in the form of a time series or annual data for a period of 5 years from 2018-2019. This information is taken from the official website of the Central Statistics Agency. The purpose of this observation is to identify patterns of association with economic growth and the level of open poverty in Indonesia over a certain period of time. This research uses macroeconomic data, including GDP and open poverty levels, collected from trusted sources. A simple linear regression analysis approach is needed to determine whether a significant correlation or effect is found between economic development and the level of open poverty. The research results state that the relationship between economic development has a negative influence on the level of open poverty in Indonesia.